MRI of the petromastoid canal in children. Issue 4 (1st August 2013) - Koral, Korgun; Vachha, Behroze; Gimi, Barjor; Zhang, Song; Ulualp, Seckin O.; Suter, Edgar; Fernandes, Neil; McMenamy, John; Booth, Timothy N.
Abstract : Purpose: To characterize the MRI features of the petromastoid canal in children with sensorineural hearing loss (SNHL) and in normal infants. Materials and Methods: High resolution MRI examinations of 564 children who were evaluated for SNHL and brain MRI examinations of 112 infants who had normal studies were studied independently by two reviewers. Results: In SNHL group, visibility of the PMC decreased for right and left PMC ( P < 0.001). The width of the right PMC significantly decreased as age increased ( P < 0.0001). There was no relation between abnormalities of membranous labyrinth and cochlear nerve and PMC visibility in children with SNHL (p > 0.05). In the normal group, the PMC visibility decreased with increasing age (right P = 0.0001, left P = 0.001). In the normal group also, as age increased, the PMC width decreased for both PMCs (right, P = 0.0006; left, P = 0.03). Conclusion: The PMC is more frequently visualized in young children. Its visibility and width are not associated with abnormalities of membranous labyrinth and cochlear nerves.J. Magn. Reson. Imaging 2014;39:966–971. ©2013 Wiley Periodicals, Inc.